Abstração inicial em duas bacias hidrográficas de Uberlândia/MG - Sousa, Yara Cristina Batista de (2022)
The present work aims to find an initial abstraction (iA) parameter for two watersheds in the municipality of Uberlândia, Minas Gerais, Brazil: Experimental Watershed of Córrego do Glória and Experimental Watershed of Córrego Água Vermelha (respectively BHEGL and BHEAV, in Portuguese abbreviation). The conditions of response to rainfall and production of water flow are one of the challenges in hydrographic studies. Thus, among the studies available in the area, the Number Curve (CN) method, of Soil Conservation Service – SCS, is widely used due to its practicality, based on visible boundaries, land usage, location and rainfall data, flow measurement and possible water storage, which favors better information water resources for decision-making. In addition to consulting articles, books and periodicals to understand the watershed, the hydrological cycle and the initial Abstraction, the SCS-CN method was applied to determine an iA parameter, with values calculated from rainfall and flow data from 2015 to 2021. In fact, the iA can be considered a “loss” under the conditions of increased flow rate, as it occurs through the interception and infiltration processes, which, together, indicate that not all rainfall events convert to direct flow. The average parameter of water collection from the two basins studied was lower than the value obtained by the applied methodology, which determines 20% (0.2) of water storage in the soil. Then, the results of this investigation may be relevant to estimate surface runoff and be used in studies in the hydrology and environmental management sectors, in addition to determine what can be done to avoid social and economic losses in the management of watersheds of small scale existing in several regions of Brazil